An analysis and reduction of disruptive behavior on school buses. - Greene, B F (1981)
Thousands of children are injured or killed each year in school bus accidents. A significant number of these tragic incidents is precipitated by disruptive child behavior that distracts the drivers from their difficult task. Two experiments were conducted which addressed this problem. For both experiments an automated sound recording device (referred to as a Noise Guard) selectively responsive to frequencies above 500 Hz (i.e., unresponsive to bus drone) recorded both the duration and frequency of noise outbursts above a tolerable threshold. Additionally, an observer made in situ measurements of other disruptions including roughhousing and getting-out-of-seat. In the first experiment, following baseline measurements of these behaviors, middle-school students received feedback for noise outbursts. That is, when "Noise Guard" was activated, it in turn operated one of several lights on a panel visible to all passengers. Each day students were allowed to listen to high-appeal taped music while riding the bus and to participate in a raffle for prizes, provided the number of outbursts on the preceding day remained below a specified criterion indicated on the light panel. This intervention resulted in drastic reductions of noise outbursts with a concomitant reduction in other disruptive behaviors. Comparable results were obtained in the second experiment which eliminated the raffle from the intervention.